2017
DOI: 10.1007/s11356-017-0262-1
|View full text |Cite
|
Sign up to set email alerts
|

The synergetic effects of turbulence and turbidity on the zooplankton community structure in large, shallow Lake Taihu

Abstract: Climate change is predicted to influence the heat budget of aquatic ecosystems and, in turn, affect the stability of the water column leading to increased turbulence coupled with enhanced turbidity. However, the synergetic effects of turbulence and turbidity on zooplankton community structure remain to be understood in large, shallow lakes. To determine the possible synergetic effects of these factors on zooplankton communities, a 15-day mesocosm experiment was carried out and tested under four turbulence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…The changes in zooplankton during the two sampling seasons coincided with those of the phytoplankton and are concurrent with turbidity, as reported by [37] [38]. Besides, the competition among plankton species was intensified as a result of the turbidity of the water [39]. These results are similar to that obtained by [34] which concluded that the southern part (upstream) is richer in zooplankton than the northern one (downstream), as in Figure 6, and this coincided with the increased nutrient level in the water coming with the flood [40].…”
Section: Resultssupporting
confidence: 74%
“…The changes in zooplankton during the two sampling seasons coincided with those of the phytoplankton and are concurrent with turbidity, as reported by [37] [38]. Besides, the competition among plankton species was intensified as a result of the turbidity of the water [39]. These results are similar to that obtained by [34] which concluded that the southern part (upstream) is richer in zooplankton than the northern one (downstream), as in Figure 6, and this coincided with the increased nutrient level in the water coming with the flood [40].…”
Section: Resultssupporting
confidence: 74%
“…Changes in inorganic turbidity can lead to significant shifts in community composition (Teffera et al, 2018;Zhou et al, 2018).…”
Section: Influence Of Turbidity On the Igp Systemmentioning
confidence: 99%
“…As suspended inorganic particles (e.g. clay, silt; Eiler et al, 2003) interfere with the filter-feeding process (Kirk & Gilbert, 1990), their high concentration in the water is expected to have a negative effect on zooplankters (Dejen, Vijverberg, Nagelkerke, & Sibbing, 2004;Teffera et al, 2018;Zhou, Qin, & Han, 2018). There is, however, a difference among suspension feeders in their ability of coping with (often extreme) turbid conditions.…”
mentioning
confidence: 99%
“…Although turbulence might enhance the food capture capacity of D. magna individuals 22,52,53 , at ε > ε cr , the mechanical movement was inhibited. Other authors have found turbulence to affect or disturb vertical refuge for zooplankton 54 and/or zooplankton community composition through changes in phytoplankton 55 and predation 56,57 . Therefore, high levels of turbulence will inhibit D. magna swimming, affect survival and increase the contact of D. magna individuals with their preys 4,8,58 .…”
Section: Discussionmentioning
confidence: 99%